Coordinación de robots móviles mediante un controlador-observador no lineal basado en el error de posición de las unidades móviles. (2020)
In this document we present the design of a nonlinear controller based on position and orientation error in order to coordinate the movement of two mobile robots using the leader-follower strategy. Initially, the mathematical model of the differential robot is described, expressed in terms of ordinary linear differential equations, which were simulated and validated using the Matlab software. In Chapter 3 a state observer is proposed to estimate the angular velocity of the differential robot, which will be used for the implementation of the controller. Then it is describe the controller that aims to coordinate mobile robots to follow a path described by a parametric curve, where the leading robot has the reference parametric curve incorporated which will follow the other mobile robots. Finally, remarks and conclusions are presented, taking into account obtained results and future work.